ANALISIS HASIL PEMOTONGAN RUMPUT DENGAN VARIASI KECEPATAN MOTOR - Irfan Taufikurahman (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the cutting process and the quality of the output from a grass chopper machine designed to assist farmers in improving feed preparation efficiency. The machine was tested at varying blade rotation speeds (RPM) to determine the optimal performance for chopping elephant grass. The study used ST-45 steel blades and an NGX-200 gasoline engine. The cutting process was evaluated based on output capacity, chopping fineness, and cutting time. Data were processed using ANOVA statistical methods to determine the impact of RPM variations on the quality of the cut. The results showed that increasing blade rotation speed significantly affects the chopping quality. Optimal RPM was found between 1200 and 1400, where the grass was finely chopped and ready to be mixed with additional feed. Speeds below 700 RPM produced less effective cuts, while speeds above 1800 RPM led to faster blade wear. In conclusion, cutting speed variation greatly influences the quality and efficiency of the chopping process. This research provides valuable insight for developing efficient and energy-saving grass chopper machines for small to medium-scale farmers.